Effect of shoot topping intensity on 'Cabernet Franc' grapevine maturity in high-altitude region - Wurz D.A.* (2017)
The objective of this work was to evaluate the chemical composition of 'Cabernet Franc' grape subjected to different levels of shoot topping. The experiment was conducted in the 2008 and 2009 vintages, and the levels of shoot topping consisted of: control, without topping; and reductions of 15, 30, and 45% in total leaf area. The effect of shoot topping intensity on the chemical composition of the 'Cabernet Franc' grape berries was observed. A reduction of 26% in the vegetative canopy through a moderate shoot topping increased the total polyphenol index and the anthocyanin content. Shoot topping is a practice that must be carried out with caution, since severe shoot topping, i.e., a reduction greater than 26% of the leaf area, may negatively impact grape quality by reducing the content of soluble solids and decreasing the total polyphenol index and the content of anthocyanins of 'Cabernet Franc' grape berries.